Trapping of Terminal Platinapolyynes by Copper(I) Catalyzed Click Cycloadditions; Probes of Labile Intermediates in Syntheses of Complexes with Extended sp Carbon Chains, and Crystallographic Studies - Amini, Hashem; Weisbach, Nancy; Gauthier, Sebastien; Kuhn, Helene; Bhuvanesh, Nattamai; Hampel, Frank; Reibenspies, Joseph H.; Gladysz, John A. (Chemistry - A European Journal, 2021)
The silylated hexatriynyl complex trans-(C6F5)(p-tol3P)2Pt(C≡C)3SiEt3 (PtC6TES) is converted in situ to PtC6H (wet n-Bu4N+ F−, THF) and cross coupled with the diyne H(C≡C)2SiEt3 (HC4TES; CuCl/TMEDA, O2) to give PtC10TES (71 %). This sequence is repeated twice to afford PtC14TES (65 %) and then PtC18TES (27 %). An analogous series of reactions starting with PtC8TES gives PtC12TES (60 %), then PtC16TES (43 %), and then PtC20TES (17 %). Similar cross couplings with H(C≡C)2Si(i-Pr)3 (HC4TIPS) give PtC12TIPS (68 %), PtC14TIPS (68 %), and PtC16TIPS (34 %). The trialkylsilyl species (up to PtC18TES) are converted to 3+2 “click” cycloadducts or 1,4-disubstituted 1,2,3-triazoles trans-(C6F5)(p-tol3P)2Pt(C≡C)n-1C=CHN(CH2C6H5)N=N (29–92 % after workups). The most general procedure involves generating the terminal polyynes PtCxH (wet n-Bu4N+ F−, THF) in the presence of benzyl azide in DMF and aqueous CuSO4/ascorbic acid. All of the preceding complexes are crystallographically characterized and the structural and spectroscopic properties analyzed as a function of chain length. Two pseudopolymorphs of PtC20TES are obtained, both of which feature molecules with parallel sp carbon chains in a pairwise head/tail packing motif with extensive sp/sp van der Waals contacts.
CRIS-Team Scopus Importer:2021-07-30
Keywords: alkyne cross-coupling; click reaction; crystal structures; platinum; polyyne; protodesilylation